PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM : Studi Empiris Pada Industri Pariwisata dan Rekreasi Yang Terdaftar Di BEI - Shafa Almira (2021)
This research is a quantitive research that aims to analyze the influence of financial performance on share price in tourism and recreation industry listed on the Indonesia Stock Exchange for the period 2016-2019. The sample of this study used 14 companies, the sample selection used a purposive sampling technique. The data analysis technique used panel data regression models. The results of this study shows that ROA and DER has a significant positive effect, while CR has no significant effect on share price.